ANALISIS PERILAKU HIKIKOMORI PADA TOKOH TAMOTSU TADOKORO DALAM MANGA FUTSUTSUKA MONO NO ANI DESU GA KARYA HIGURASHI KINOKO - Dinda Puan Maharani; Ari Artadi; Riri Hendriati (Universitas Diponegoro, 2024)
Hikikomori is one of the social problems in Japan. A research on the hikikomori behavior of Tamotsu Tadokoro in Higurashi Kinoko's Manga Futsutsuka Mono no Ani Desu ga was conducted. The purpose of this research is to know and explain the forms of behavior, and factors that cause hikikomori behavior and to find out and explain the efforts made by the character Tamotsu Tadokoro in the Comic series